PENGARUH BUDAYA ORGANISASI DAN IKLIM ORGANISASI TERHADAP LOYALITAS KERJA KARYAWAN (STUDI KASUS PADA PT. BANK NEGARA INDONESIA KCU PEKANBARU) - Ardiansyah "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of Organizational Culture and Organizational Climate on Employee loyalty (Case Study at PT. Bank Negara Indonesia KCU Pekanbaru).Organizational Culture as a variable ( X1 ) Organizational Climate as a variable ( X2 ) and Employee Loyalty as ( Y ).The method in this research is descriptive and quantitative using SPSS 20. The samples used were 69 employees. To determine the sample using census study . Data collection through questionnaires .Results of analysis using multiple linear regression , t test , and test f . It can be seen that the Organizational Culture variables significantly influence Employee Loyalty , Organizational Climateeffect on Employee Loyalty , and Organizatonal Culture and Organizational Climate significant effect on Employee LoyaltyKeywords : Organizational Culture, Organizational Climate, and Employee Loyalty